Interferon gamma/NADPH oxidase defense system in immunity and cancer. (1st February 2016) - Hodny, Zdenek; Reinis, Milan; Hubackova, Sona; Vasicova, Pavla; Bartek, Jiri
ABSTRACT: As a part of cellular pathogen defense, IFNγ triggers induction of NADPH oxidase NOX2, which produces superoxide into phagosomes of immune cells. Recent data show that a similar mechanism can also operate in IFNγ-mediated anticancer control. IFNγ is capable of inducing expression of constitutively active NADPH oxidase NOX4 in tumor cells leading to generation of reactive oxygen species (ROS) damaging DNA, activation of DNA damage response and cell cycle arrest/premature cellular senescence.